2015
DOI: 10.5032/jae.2015.02027
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Perceptions of Visual Communications Curriculum in Arkansas Secondary Agricultural Classrooms: A Closer Look at Experiential Learning Integrations

Abstract: The University of Arkansas developed and integrated visual communications curriculum related to agricultural communications into secondary agricultural programs throughout the state. The curriculum was developed, pilot tested, revised, and implemented by selected secondary agriculture teachers. The primary purpose of this study was to evaluate students' knowledge prior to the program, after the curriculum was taught, and after participation in a day-long experiential learning activity utilizing skills and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Although the results from these studies seem promising, research is lacking to confirm the effectiveness of visual communications, including infographics, used in the context of educational materials (Lyra et al 2016). In agricultural education, Pennington et al (2015) called for an expansion of visual communications use in the discipline and additional research on the impact visual communications has on agricultural education efforts. This study was conducted to evaluate what influence infographics could have on helping people learn more about agricultural topics and retain that information.…”
Section: The Effect Of Infographics On Recall Of Information About Gementioning
confidence: 99%
“…Although the results from these studies seem promising, research is lacking to confirm the effectiveness of visual communications, including infographics, used in the context of educational materials (Lyra et al 2016). In agricultural education, Pennington et al (2015) called for an expansion of visual communications use in the discipline and additional research on the impact visual communications has on agricultural education efforts. This study was conducted to evaluate what influence infographics could have on helping people learn more about agricultural topics and retain that information.…”
Section: The Effect Of Infographics On Recall Of Information About Gementioning
confidence: 99%
“…Furthermore, longer studies may increase mortality rates that could interfere with statistical significance. Seven studies suggested follow-up research using experimental design extend the duration of the treatment (Baker et al, 2014;Baker & Robinson, 2016;Bunch et al, 2014;Burris & Garton, 2007;Parr et al, 2006;Pennington et al, 2015;Rose et al, 2015).…”
Section: Research Question 5: What Trends In Research Recommendationsmentioning
confidence: 99%
“…Six studies recommended future research in experimental design investigate long-term knowledge retention of subjects exposed to treatments (Baker et al, 2014;Bunch et al, 2014;Myers & Dyer, 2006;Pennington et al, 2015;Sapp & Thoron, 2014;Wagler, et al, 2008).…”
Section: Research Question 5: What Trends In Research Recommendationsmentioning
confidence: 99%
“…Myers & Dyer, 2006;Pennington et al, 2015;Sapp & Thoron, 2014;Wagler, et al, 2008).Colclasure & Thoron Experimental Studies in School-based Agricultural Education…Journal of Agricultural Education…”
mentioning
confidence: 99%